(untitled) (Journal of Oriental Studies, 2017)
This article describes the reasons for creation of low-carbon society in Japan and its basic concept. The basic characteristics and key indicators of the concept have been considered. Two scenarios for developing a lowcarbon society in Japan by 2050 and its positive effects were analysed. In addition, the article shows the modern achievements of Japan in the implementation of the low-carbon society concept.